KASTURI ORANGE PEEL (CITRUS MICROCARPA BUNGE) ESSENTIAL OIL: CHEMICAL PROFILE, FORMULATION AS ROLL-ON AROMATHERAPY AND ITS EVALUATION - RASYADI, YAHDIAN; NINGSIH, WIDA; MULYA, WANDA PRANCA; HANIFA, DINI (International Journal of Applied Pharmaceutics, 2024)
Objective: Kasturi orange (Citrus microcarpa Bunge) is widely cultivated and consumed in Indonesia. The fruit's flesh is a good source of vitamin C. Essential oil of kasturi orange peel is one of the ingredients used as a raw material for aromatherapy roll-on preparations. Roll-on aromatherapy is currently widely used by various age groups. This research aims to determine the content of kasturi oil, its formulation as a roll-on aromatherapy preparation, and its physical evaluation. Methods: The essential oil of kasturi orange peel was extracted using the distillation method, and then the physicochemical properties were examined. The chemical content of the oil was analyzed using GC-MS. The roll-on aromatherapy preparation formulas were made by varying concentrations of kasturi oil, F0 (0%), F1 (4%), F2 (6%), and F3 (10%). Additional substances used were menthol, camphor, patchouli oil, and virgin coconut oil. Patchouli oil was used in this preparation to make the aroma last longer. Evaluation of roll-on aromatherapy preparations includes organoleptic tests, pH tests, specific gravity, viscosity, clarity, and stability. Results: From the extraction results, the percentage yield of essential kasturi oil was 0.55% v/w, with a density of 0.85 g/ml and a refractive index of 1.469. From the chromatogram results, there were 18 compounds in kasturi oil; the largest component was D-limonene (32.59%). Physical evaluation results of all roll-on aromatherapy formulas had met the requirements. Conclusion: From the chromatogram results, there were 18 compounds in kasturi oil, with the largest component were D-limonene (32.59%). Formula F3 had the best aroma intensity, approximately for 5 h, with a slightly strong aroma, and physical evaluation results of all roll-on aromatherapy formulas had met the requirements.